A phase I trial of the trifunctional anti Her2 × anti CD3 antibody ertumaxomab in patients with advanced solid tumors. Issue 1 (December 2016) - Haense, N.; Atmaca, A.; Pauligk, C.; Steinmetz, K.; Marmé, F.; Haag, G.; Rieger, M.; Ottmann, O.; Ruf, P.; Lindhofer, H.; Al-Batran, S.-E.
Abstract Background Ertumaxomab (ertu) is a bispecific, trifunctional antibody targeting Her2/neu, CD3 and the Fcγ-receptors I, IIa, and III forming a tri-cell complex between tumor cell, T cell and accessory cells. Methods Patients (pts) with Her2/neu (1+/SISH positive, 2+ and 3+) expressing tumors progressing after standard therapy were treated to investigate safety, tolerability and preliminary efficacy. In this study, ertu was applied i.v. in 2 cycles following a predefined dose escalating scheme. Each cycle consisted of five ascending doses (10–500 μg) applied weekly within 28 days with a 21 day treatment-free interval. If 2 pts experienced a dose limiting toxicity (DLT) at a given dose level, the maximum tolerated dose (MTD) had been exceeded. Results Fourteen heavily pretreated pts (e.g. breast, rectal, gastric cancer) were enrolled in the four main cohorts. Three (21 %) pts had to be replaced. Two serious adverse events (SAE) with possible relation to the investigational drug were seen, both fully reversible. A DLT was not detected. Consequently, the MTD could not be determined. All adverse events (AE) were transient and completely reversible. Most frequent AEs were fatigue (14/14), pain (13/14), cephalgia (12/14), chills (11/14), nausea (8/14), fever (7/14), emesis (7/14) and diarrhea (5/14). Single doses up to 300 μg were well tolerated (total dose up to 800 μg per cycle). We observed one partial remission and two disease stabilizations after first treatment cycle. Conclusions Single doses up to 300 μg could be safely administered in an escalating dose scheme. Immunological responses and clinical activity warrant further evaluation in patients with Her2 over expressing tumors. Trial registration EudraCT number: 2011-003201-14; ClinicalTrials.gov identifier:NCT01569412